PENGARUH MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PT. BINAYA INDO JAYA JOMBANG - Serang, Abdurahman; Kuswinarno, Mudji (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
Motivation is a mental drive that influences human behavior based on their needs. This study aims to identify the impact of work motivation on employee performance, with organizational citizenship behavior as an intervening variable, among employees of PT Binaya Indo Jaya Jombang. The research method employs a quantitative approach with a population of 115 respondents. The sample uses a probability simple random sampling method, consisting of 89 respondents. Data were collected through interviews and questionnaires. The data analysis techniques used included multiple linear regression and path analysis. Hypothesis testing involved reliability, validity, normality, multicollinearity, heteroscedasticity, partial t, simultaneous f, and coefficient of determination (R2) tests. The results of this study are: The study found that work motivation has a positive and significant effect on employee performance (t=14.918, p0.05) and organizational citizenship behavior (t=5.725, p0.05). Organizational citizenship behavior (OCB) has a positive and significant impact on employee performance (t=5.927, p0.05). Work motivation indirectly affects employee performance through OCB, with a direct effect value of 14.918 and an indirect effect value of 33.932. Keywords: Work Motivation, Employee Performance, Organizational Citizenship Behavior